Non-Unionid Freshwater Bivalves (Sphaeriidae, Corbiculidae, Dreissenidae) of North American Fauna - Korniushin, A.V. (Вестник зоологии, 2007)
The article concerns recent representatives of the North American freshwater bivalve mollusks from the three families: Sphaeriidae, Corbiculidae and Dreissenidae. Since only the first family contains aborigine North American species, the paper is focused on this group. The Corbiculidae are represented by a single species (Corbicula fluminea) and Dreissenidae by two species (Dreissena polymorpha and D. bugensis) introduced from Europe and Asia.